Increasing the Stability of Dental Implants: the Concept of Osseodensification - Podaropoulos Leonidas (Balkan Stomatological Society, 2017)
One of the most important factors that affect osseointegration is the primary stability of the implant. Dental implants inserted at the posterior region of the maxilla exhibit the lowest success rates as the low density bone in this area often jeopardize rigid fixation of the implant. Many surgical techniques have been developed to increase the primary stability of an implant placed in low density bone, such as bicortical fixation of the implant, undersized preparation of the implant bed and bone condensation by the use of osteotomes. A new promising technique, named osseodensification, has been recently developed that creates an autograft layer of condensed bone at the periphery of the implant bed by the aid of specially designed burs rotating in a clockwise and anti-clockwise direction. The purpose of this review is to emphasize that implant primary stability is strongly influenced by the surgical technique, to quote and briefly analyse the various surgical procedures laying weight to osseodensification procedure.